Wet ball milling method for enhancing waste cathode carbon leaching impurity removal and carbon nanosheet generation
By combining wet ball milling and chemical leaching, the problems of removing harmful substances from waste cathode carbon and preparing carbon nanosheets were solved, the preparation of high-purity carbon nanosheets was achieved, and high-quality raw material support was provided.
Patent Information
- Application Number
- CN202511002755.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-10-17
AI Technical Summary
Existing technologies make it difficult to effectively remove harmful substances from waste cathode carbon and prepare high-purity carbon nanosheets, especially because the electrolyte is difficult to remove due to the large particle size of the carbon powder, and wet processing poses a risk of secondary pollution.
The wet ball milling method combined with the chemical leaching method is used to prepare high-purity carbon nanosheets by refining the carbon powder through ball milling and chemically treating it in an acid-base solution.
It significantly inhibits material agglomeration, obtains carbon nanosheets with smaller particle size and higher purity, reduces equipment wear and material loss, provides high-quality raw material guarantee, and has a simple and environmentally friendly process.
Smart Images

Figure CN120793905A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of solid waste resource utilization, and particularly relates to a wet ball milling method for enhancing leaching and impurity removal of waste cathode carbon and generating carbon nanosheets. BACKGROUND
[0002] As a large aluminum producer, China increases the production and capacity every year. The aluminum electrolysis cell is continuously eroded and penetrated by electrolyte in the production process, which leads to deformation and rupture and thus cannot work normally. Therefore, overhaul must be carried out. A part of solid waste produced in the overhaul process includes waste cathode carbon, which contains a large amount of soluble fluorine and a small amount of cyanide. Random open-air placement or burial can cause harm to the ecological environment and human beings, so it is of great significance to treat the waste cathode carbon.
[0003] At present, the methods for harmless treatment of waste cathode carbon mainly include wet method and fire method (roasting, molten salt roasting and high temperature distillation); the wet method includes physical method (water immersion, flotation) and chemical leaching method (acid, alkali and synergistic leaching). Among them, the physical method has simple process and low cost, and can separate or remove most of the harmful substances in the waste cathode carbon, but still cannot meet the emission requirements; the fire method has high treatment cost and produces toxic gas, which limits its industrial popularization in reality; the chemical leaching method produces acid leaching waste liquid and alkali leaching waste liquid, which can cause secondary pollution. The methods for harmless treatment of waste cathode carbon have advantages and disadvantages. Considering that the wet method can recover the valuable component carbon and separate and recycle the electrolyte, the present application selects this method for impurity removal. However, the particle size of the carbon powder selected by the previous wet method is large, so it is difficult to remove the electrolyte in the carbon powder. Therefore, it is necessary to find an effective method to fully expose the electrolyte and obtain carbon nanosheets with high purity, and ball milling is a better test method at present. The wet ball milling effectively avoids material aggregation; compared with dry milling, wet milling is beneficial to more complete crushing of the material and obtaining powder with smaller particle size. At the same time, it has smaller wear and material loss, so as to prepare carbon nanosheets with good dispersity and provide better raw material guarantee for the development of carbon materials. SUMMARY
[0004] In view of the above problems, the present application aims to provide a wet ball milling method for enhancing leaching and impurity removal of waste cathode carbon and generating carbon nanosheets, which refines the carbon powder by ball milling and purifies the waste cathode carbon powder under the assistance of chemical leaching method, so as to obtain carbon nanosheets.
[0005] In order to achieve the above technical purposes, the present application adopts the following technical solutions:
[0006] The wet ball milling method for enhancing leaching and impurity removal of waste cathode carbon and generating carbon nanosheets is characterized in that high-purity carbon nanosheets are obtained by using waste cathode carbon as raw material and adopting the method of wet ball milling and chemical leaching.
[0007] Further, the wet ball milling method for enhancing waste cathode carbon leaching and generating carbon nanosheets, comprising the following steps:
[0008] (1) Coarsely crushing, finely crushing, and pulverizing the aluminum electrolysis waste cathode carbon block;
[0009] (2) Placing the waste cathode carbon powder of step (1) and a grinding solvent in a ball mill in a certain proportion, setting the ball milling parameters, and then ball milling to obtain a suspension of balls and slurry;
[0010] (3) Adding a certain amount of water to the suspension to separate the balls and the slurry, and then performing suction filtration on the obtained suspension to obtain filter cake A;
[0011] (4) Dispersing filter cake A into an acidic solution, stirring at a corresponding temperature for a certain period of time, and then performing suction filtration to obtain filter cake B;
[0012] (5) Dispersing filter cake B into an alkaline solution, stirring at a corresponding temperature for a certain period of time, and then performing suction filtration to obtain filter cake C;
[0013] (6) Washing filter cake C with water and performing suction filtration, and then drying to obtain purified carbon nanosheets.
[0014] Preferably, the grinding solvent is water.
[0015] Preferably, the mass ratio of waste cathode carbon powder to grinding solvent is 1:24-1:2.
[0016] Preferably, the ball milling parameters include ball milling speed, ball milling time, and ball size.
[0017] Preferably, the ball milling speed is 150 r / min-800 r / min.
[0018] Preferably, the ball milling time is 1 h-24 h.
[0019] Preferably, the ball size is 0.4 mm-10 mm.
[0020] Preferably, the amount of water for ball and slurry separation is 100 mL-400 mL.
[0021] Preferably, the acid solution is hydrochloric acid.
[0022] Preferably, the concentration of the hydrochloric acid is 1 mol / L-12 mol / L.
[0023] Preferably, the acid leaching temperature is 25-90°C.
[0024] Preferably, the acid leaching time is 1 h-10 h.
[0025] Preferably, the alkali solution is a sodium hydroxide solution.
[0026] Preferably, the sodium hydroxide concentration is 0.5-5 mol / L.
[0027] Preferably, the alkali leaching temperature is 25-90℃.
[0028] Preferably, the alkali leaching time is 1-10h.
[0029] Preferably, the filter cake C is washed with 400 mL of water in 4 equal portions, and then dried to obtain purified carbon nanosheets.
[0030] Preferably, the carbon purity after purification is greater than 93%, and the carbon nanosheet particle size is about 458.7 nm, and the distribution range is narrowed.
[0031] Compared with the prior art, the present application has the following technical advantages:
[0032] (1) The ball milling process adopted by the present application can significantly inhibit the material aggregation phenomenon. Compared with dry grinding, wet grinding not only makes the material crushing more sufficient, obtains finer powder, but also reduces equipment wear and material loss, thereby preparing carbon nanosheets with excellent dispersion performance, laying a solid foundation for the research and development of carbon material field.
[0033] (2) The carbon nanosheets prepared by the method of the present application have considerable purity, and the whole process is based on cheap raw materials, and the process is simple and easy to operate. In the harmless treatment and resource utilization of waste cathode carbon, this method shows broad application potential and development prospect. BRIEF DESCRIPTION OF DRAWINGS
[0034] Figure 1 is a comparison chart of carbon nanosheets and their calcined ash;
[0035] Figure 2 is a dispersion comparison chart of original carbon powder and ball-milled carbon powder suspension;
[0036] Figure 3 is an X-ray diffraction spectrum of original carbon powder and carbon nanosheets;
[0037] Figure 4 is a scanning electron microscope image of original carbon powder and carbon nanosheets;
[0038] Figure 5 is a particle size distribution chart of original carbon powder and carbon nanosheets. DETAILED DESCRIPTION
[0039] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be described in detail below with reference to its embodiments. It should be understood that the specific embodiments described herein are merely intended to demonstrate and explain the present application, and do not limit the protection scope of the present application.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the description of the application herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0041] The present application provides a wet ball milling method for enhancing impurity removal and generating carbon nanosheets from waste cathode carbon, comprising the following steps:
[0042] (1) placing waste cathode carbon powder and a grinding aid solvent in a ball mill device in a certain proportion for ball milling treatment, and then obtaining a suspension of balls and slurry;
[0043] (2) diluting the suspension with water, and then separating the suspension and the grinding balls;
[0044] (3) suction filtering the suspension to obtain filter cake A;
[0045] (4) dispersing the filter cake A into a plastic beaker containing a certain volume and concentration of hydrochloric acid solution, stirring under heating for a certain time, and suction filtering the suspension to obtain filter cake B;
[0046] (5) dispersing the filter cake B into a plastic beaker containing a certain volume and concentration of sodium hydroxide solution, stirring under heating for a certain time, and suction filtering the suspension to obtain filter cake C;
[0047] (6) rinsing and suction filtering the filter cake C with 400 mL of water in four equal parts, and obtaining purified carbon nanosheets through drying treatment.
[0048] The waste cathode carbon powder purification method in the above scheme is simple, the overall preparation process parameters are mild, and carbon nanosheets with uniform size, small particle size and high purity can be obtained.
[0049] In one embodiment, the grinding aid solvent is water.
[0050] In one embodiment, the mass ratio of the waste cathode carbon powder to water is 1:24-1:2.
[0051] In one embodiment, the ball milling parameters include ball milling speed, ball milling time and grinding ball size.
[0052] In one embodiment, the ball milling rotation speed is 150 r / min-800 r / min.
[0053] In one embodiment, the ball milling time is 1 h-24 h.
[0054] In one embodiment, the ball milling tank is placed with grinding balls, and the size of the grinding balls is 0.4 mm-10 mm.
[0055] In one embodiment, the grinding balls are composed of any one of zirconia, ceramic, agate and stainless steel.
[0056] The embodiments of the present application will be described in detail below with specific examples.
[0057] Example 1:
[0058] A wet ball milling method for enhancing impurity removal and generating carbon nanosheets from waste cathode carbon, comprising the following steps:
[0059] A vertical planetary ball mill (Yueyang Keda Equipment Co., Ltd., DECO-PBM-V-2L) was used to place 2 g of waste cathode carbon powder and 24 g of water in a centrifuge tube, shake well, and then pour into an agate ball milling tank. The size of the zirconia balls in the agate ball milling tank was 1.0-1.2 mm, the weight of the grinding balls was 150 g, the rotation speed was 400 r / min, and the ball milling time was 6 h (the setting mode of the ball milling time was 2 h of forward rotation, followed by 2 h of reverse rotation, and the forward and reverse rotation was alternately performed). Then a suspension of balls and slurry was obtained. The suspension was washed with 100 mL of water in small amounts and multiple times to obtain a slurry, which was suction filtered to obtain a filter cake A; the filter cake A was dispersed in 20 mL of a hydrochloric acid solution with a concentration of 1.5 mol / L, stirred at 80°C for 1 h, and then suction filtered to obtain a filter cake B; the filter cake B was dispersed in 20 mL of a sodium hydroxide solution with a concentration of 2.5 mol / L, stirred at 80°C for 1 h, and then suction filtered to obtain a filter cake C; the filter cake was washed with 400 mL of water in equal amounts of 4 times, and then dried to obtain carbon nanosheets. The ash content detection results are shown in Table 1.
[0060] Example 2:
[0061] A wet ball milling method for enhancing impurity removal and generating carbon nanosheets from waste cathode carbon, comprising the following steps:
[0062] A vertical planetary ball mill (Yueyang Deco Equipment Co., Ltd., DECO-PBM-V-2L) was used to mill 5 g of waste cathode carbon powder in a agate mill jar. Zirconia balls with a size of 1.0-1.2 mm were used in the mill jar, and the weight of the balls was 150 g. The rotation speed was 400 r / min, and the milling time was 6 h (2 h forward rotation, 2 h reverse rotation, and the two processes were repeated alternately). A suspension containing the balls was obtained. The suspension was washed with 100 mL of water for several times, and the slurry was filtered to obtain filter cake A. Filter cake A was dispersed in 50 mL of 1.5 mol / L hydrochloric acid solution, and stirred at 80°C for 1 h. The filter cake B was obtained by filtration. Filter cake B was dispersed in 50 mL of 2.5 mol / L sodium hydroxide solution, and stirred at 80°C for 1 h. The filter cake C was obtained by filtration. The filter cake was washed with 400 mL of water for four times, and dried to obtain carbon nanosheets. The ash content of the carbon nanosheets was determined, and the results are shown in Table 1.
[0063] Example 3
[0064] A wet ball milling method for enhancing the leaching and impurity removal of waste cathode carbon and generating carbon nanosheets, comprising the following steps:
[0065] A vertical planetary ball mill (Yueyang Deco Equipment Co., Ltd., DECO-PBM-V-2L) was used to mill 5 g of waste cathode carbon powder in a agate mill jar. Zirconia balls with a size of 1.0-1.2 mm were used in the mill jar, and the weight of the balls was 150 g. The rotation speed was 400 r / min, and the milling time was 6 h (2 h forward rotation, 2 h reverse rotation, and the two processes were repeated alternately). A suspension containing the balls was obtained. The suspension was washed with 100 mL of water for several times, and the slurry was filtered to obtain filter cake A. Filter cake A was dispersed in 50 mL of 1.5 mol / L hydrochloric acid solution, and stirred at 80°C for 1 h. The filter cake B was obtained by filtration. Filter cake B was dispersed in 50 mL of 2.5 mol / L sodium hydroxide solution, and stirred at 80°C for 1 h. The filter cake C was obtained by filtration. The filter cake was washed with 400 mL of water for four times, and dried to obtain carbon nanosheets. The ash content of the carbon nanosheets was determined, and the results are shown in Table 1.
[0066] Example 4
[0067] A wet ball milling method for enhancing the leaching and impurity removal of waste cathode carbon and generating carbon nanosheets, comprising the following steps:
[0068] A vertical planetary ball mill (Yueyang Deco Equipment Co., Ltd., DECO-PBM-V-2L) was used to mix 2 g of waste cathode carbon powder and 24 g of water in a centrifuge tube, and then pour into a agate ball mill tank. The size of the zirconia balls in the agate ball mill tank was 1.0-1.2 mm, and the weight of the grinding balls was 150 g. The ball milling was carried out at a speed of 200 r / min for 6 h (the setting mode of the ball milling time was 2 h of forward rotation, followed by 2 h of reverse rotation, and the forward and reverse rotation were alternately performed). Then a suspension of balls and slurry was obtained. The suspension was washed with 100 mL of water in small amounts and multiple times to obtain a slurry, which was suction filtered to obtain a filter cake A. The filter cake A was dispersed in 20 mL of a hydrochloric acid solution with a concentration of 1.5 mol / L, stirred at 80°C for 1 h, and then suction filtered to obtain a filter cake B. The filter cake B was dispersed in 20 mL of a sodium hydroxide solution with a concentration of 2.5 mol / L, stirred at 80°C for 1 h, and then suction filtered to obtain a filter cake C. The filter cake was washed with 400 mL of water in equal amounts of 4 parts, and then dried to obtain carbon nanosheets. The ash content detection results are shown in Table 1.
[0069] Example 5:
[0070] A wet ball milling method for enhancing the leaching and impurity removal of waste cathode carbon and generating carbon nanosheets, comprising the following steps:
[0071] A vertical planetary ball mill (Yueyang Deco Equipment Co., Ltd., DECO-PBM-V-2L) was used to mix 2 g of waste cathode carbon powder and 24 g of water in a centrifuge tube, and then pour into a agate ball mill tank. The size of the zirconia balls in the agate ball mill tank was 1.0-1.2 mm, and the weight of the grinding balls was 150 g. The ball milling was carried out at a speed of 200 r / min for 6 h (the setting mode of the ball milling time was 2 h of forward rotation, followed by 2 h of reverse rotation, and the forward and reverse rotation were alternately performed). Then a suspension of balls and slurry was obtained. The suspension was washed with 100 mL of water in small amounts and multiple times to obtain a slurry, which was suction filtered to obtain a filter cake A. The filter cake A was dispersed in 20 mL of a hydrochloric acid solution with a concentration of 1.5 mol / L, stirred at 80°C for 1 h, and then suction filtered to obtain a filter cake B. The filter cake B was dispersed in 20 mL of a sodium hydroxide solution with a concentration of 2.5 mol / L, stirred at 80°C for 1 h, and then suction filtered to obtain a filter cake C. The filter cake was washed with 400 mL of water in equal amounts of 4 parts, and then dried to obtain carbon nanosheets. The ash content detection results are shown in Table 1.
[0072] Example 6:
[0073] A wet ball milling method for enhancing the leaching and impurity removal of waste cathode carbon and generating carbon nanosheets, comprising the following steps:
[0074] A vertical planetary ball mill (Yueyang Deco Equipment Co., Ltd, DECO-PBM-V-2L) was used to mill 2 g of the spent cathode carbon powder and 24 g of water in a centrifuge tube, which was then poured into a maroon ball mill tank. Zirconia balls with a size of 0.4-0.6 mm were used in the maroon ball mill tank, and the weight of the grinding balls was 150 g. The ball milling was performed at a rotation speed of 400 r / min for 6 h (the ball milling time was set in a manner that the rotation was performed for 2 h, followed by reverse rotation for 2 h, and the rotation and reverse rotation were alternately performed). Then, a suspension of the balls and the slurry was obtained. The suspension was washed with 100 mL of water in multiple small amounts, and the obtained slurry was subjected to suction filtration to obtain a filter cake A. The filter cake A was dispersed in 20 mL of a hydrochloric acid solution with a concentration of 1.5 mol / L, and stirred at 80°C for 1 h. Then, suction filtration was performed to obtain a filter cake B. The filter cake B was dispersed in 20 mL of a sodium hydroxide solution with a concentration of 2.5 mol / L, and stirred at 80°C for 1 h. Then, suction filtration was performed to obtain a filter cake C. The filter cake was washed with 400 mL of water in equal amounts of four portions, and then dried to obtain carbon nanosheets. The ash content detection results are shown in Table 1.
[0075] Table 1:
[0076]
[0077] As can be seen from the data in Table 1, the carbon nanosheets with an ash content of 6.15% were obtained under the optimal treatment conditions (Example 1). When the spent cathode carbon powder was not added with a grinding solvent (Example 2), the ash content was 10.36%. When the carbon / water mass ratio was increased (Example 3), the ash content increased to 9.24%. When the rotation speed was low (Example 4), the ash content was 8.06%. When the ball milling time was reduced (Example 5), the ash content was 6.57%. When the size of the grinding balls was reduced (Example 6), the ash content was 7.17%.
[0078] Figure 2 A dispersion comparison chart of the suspension of the original carbon powder and the ball milled carbon powder is given. In the chart, #1, #2, #3 and #4 are the changes in the suspension state of the ball milled carbon powder after standing for 0-30 min, and #5 is the suspension state of the original carbon powder after standing for 30 min. It can be seen that a part of #1-#4 is still suspended after standing for 30 min, and is not completely settled, while #5 is almost completely settled, which may be caused by the reduction in the particle size of the carbon powder after ball milling.
[0079] Figure 3 The X-ray diffraction spectra of the original carbon powder and the carbon nanosheets are given in FIG. 2. It can be seen that the impurities in the original carbon powder are effectively removed after ball milling and chemical leaching.
[0080] Figure 4 The scanning electron microscope images of the original carbon powder and the carbon nanosheets are given in FIG. 3. Figure 4 It can be seen from FIG. 3a that the spent cathode carbon powder is in the form of blocky particles under a magnification of 2000 times. It can be seen from FIG. 3b that the carbon nanosheets are in the form of sheets under a magnification of 2000 times. Figure 4It can be seen that the purified carbon nanometer by ball milling is in sheet shape under 40000 times magnification.
[0081] Figure 5 It can be seen from the particle size distribution that the particle size distribution of the ball-milled carbon powder is shifted to the left compared to the overall particle size distribution of the original carbon powder, indicating that the ball-milled carbon powder not only improves the purification effect but also reduces the particle size of the carbon powder.
[0082] The technical features of the above-described embodiments can be combined in any manner. To make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as the combinations of the technical features do not exist, they should be considered as falling within the scope of the present disclosure.
[0083] The above-described embodiments only express several embodiments of the present application, and the description is more specific and detailed, but it should not be understood as limiting the scope of the patent. It should be pointed out that for ordinary skilled in the art, without departing from the concept of the present application, a number of variations and improvements can be made, which are within the scope of the present application. Therefore, the scope of the patent of the present application should be subject to the appended claims.
Claims
1. A wet ball milling method for enhancing carbon leaching and impurity removal of spent cathodes and generating carbon nanosheets, characterized in that: Using waste cathode carbon as raw material, high-purity carbon nanosheets were obtained by wet ball milling combined with chemical leaching.
2. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 1, characterized in that: The steps include: (1) crushing, fine crushing and grinding the waste cathode carbon blocks from aluminum electrolysis; (2) placing the waste cathode carbon powder and the grinding solvent in the above step (1) in a ball mill according to a certain ratio, setting the ball milling parameters and performing ball milling to obtain a suspension of balls and slurry; (3) adding a certain amount of water to the suspension to separate the pellets, and then filtering the obtained suspension to obtain filter cake A; (4) Dispersing filter cake A into an acidic solution, stirring and reacting at a corresponding temperature for a certain time, and then filtering to obtain filter cake B; (5) Dispersing filter cake B in an alkaline solution, stirring and reacting at a corresponding temperature for a certain time, and then filtering to obtain filter cake C; (6) The filter cake C is rinsed with water and filtered, and then dried to obtain purified carbon nanosheets.
3. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 2, characterized in that: The particle size of the waste cathode carbon powder is above 100 meshes.
4. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 2, characterized in that: The grinding aid solvent is water, and the mass ratio of the waste cathode carbon powder to the grinding aid solvent is 1:24-1:
2.
5. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 2, characterized in that: The ball milling parameters include ball milling speed, ball milling time and grinding ball size; the ball milling speed is 150r / min-800r / min; the ball milling time is 1h-24h; and the grinding ball size is 0.4mm-10mm.
6. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 2, characterized in that: The amount of water used for ball material separation is 100mL-400mL.
7. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 2, characterized in that: The acidic solution includes one or more of hydrochloric acid and nitric acid; the acid concentration is 1 mol / L-12 mol / L; the acid leaching temperature is 25-90° C.; and the acid leaching time is 1 h-10 h.
8. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 2, characterized in that: The alkali concentration is 0.5 mol / L-5 mol / L; the alkali immersion temperature is 25-90° C.; and the alkali immersion time is 1 h-10 h.
9. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 2, characterized in that: The filter cake C was washed and filtered with 400 mL of water in four equal portions.
10. The wet ball milling method for enhancing carbon leaching and impurity removal of spent cathode and generation of carbon nanosheets according to claim 2, characterized in that: The grinding balls are made of any one of zirconium oxide, ceramics, agate and stainless steel.